LARANGAN EKSPOR CPO TERHADAP KONDISI EKONOMI DAN LINGKUNGAN - Nugraha, Daniel Widya; Sulistyono, Setyo Wahyu (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Since the implementation of the CPO export ban, there have been significant changes in the Indonesian economy and the environment surrounding oil palm plantation areas. Despite the argument that the export ban aims to increase domestic value-added and protect the environment, some preliminary studies have indicated significant negative impacts of this policy. Furthermore, the impact of the CPO export ban on Indonesia's economic growth and global market stability is also not fully understood. Therefore, a thorough analysis of the economic losses and environmental impacts of the implemented CPO export ban is required. Considering the complexity of the issue and its potential implications, an in-depth analysis of the economic losses and negative environmental impacts of the CPO export ban in Indonesia is crucial in order to develop sustainable and effective policy strategies for the palm oil sector and the economy as a whole. The research method used quantitative methods and the results and discussion concluded that when the export volume fell, it caused an increase in imports in 5 countries. The decline in CPO exports will be accompanied by a decrease in the export volume of 5 countries, it will make the country spend more money on spending, so that output sales increase which makes imports interested in importing in the country because they will get high profits or returns. Keywords: Economic Conditions, CPO Exports, Environment